2021
DOI: 10.3390/mi12010086
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Inverse Compensation of Cross-Coupling Hysteresis in Piezoceramics under Multi-Input

Abstract: In the fast tool servo (FTS) system for microstructure surface cutting, the dynamic voltage hysteresis of piezoelectric actuators (PEAs) and the cutting force produced in the manufacturing affect the driving accuracy and the cutting performance. For a multi-input-single-output (MISO) cutting system, in this paper, a dynamic hysteresis model based on a rate-dependent Prandtl–Ishlinskii model is proposed. A backpropagation neural network (BPNN) is established to describe the cross-coupling effect between the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…where xl and xa are theoretical and measured actuator displacement respectively. In microstructure surface cutting process, reaction of the dynamic cutting force on the tool is normally regarded as a disturbance to system feeding, as presented in our previous work, for the same voltage excitation, a deflection can be observed between the output hysteresis loops of a PEA with and without external load [15].…”
Section: A Verification and Analysis Of Hysteresis Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…where xl and xa are theoretical and measured actuator displacement respectively. In microstructure surface cutting process, reaction of the dynamic cutting force on the tool is normally regarded as a disturbance to system feeding, as presented in our previous work, for the same voltage excitation, a deflection can be observed between the output hysteresis loops of a PEA with and without external load [15].…”
Section: A Verification and Analysis Of Hysteresis Modelmentioning
confidence: 94%
“…After obtaining the parameters of the two dynamic PI models, the parameters w1i, w2i, bi, wi, and b are determined by neural network learning and modifications. The steepest descent backpropagation (SDBP) algorithm is used and the specific process is referred to [15].…”
Section: Parameter Identificationmentioning
confidence: 99%
“…Hu et al (2021) proposed a convolutional neural network model based on the Prandtl–Ishlinskii model, consisting of a rate-dependent Prandtl–Ishlinskii model layer and a convolutional net-work layer. Zhou et al (2021) introduced the dynamic rate of change of the input signal into the static weight of the classical PI model, forming a rate-dependent hysteresis model. At present, the rate-dependent PI hysteresis model mainly adopts the overall modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric actuators are widely used in various fields, such as atomic force microscopy [12] and nano-optics [13]. In addition, researchers have attempted to eliminate the hysteresis effect of a piezoelectric actuator by establishing various hysteresis models [14,15]. Fang et al proposed the Bouc-Wen model and identified the model parameters with the modified particle swarm optimization algorithm.…”
Section: Introductionmentioning
confidence: 99%